PENGARUH TERAPI LATIHAN DENGAN ELASTIC BAND TERHADAP KEMAMPUAN FUNGSIONAL LANSIA DENGAN OSTEOARTHRITIS LUTUT DI PSTW BUDHI MULIA 1 JAKARTA TIMUR - Rohimah, Siti; Sudarsono, Ari; Sariana, Erna (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2025)
Background: Elderly are stages of the life process of every human. Elderly the body experiences decrease in one of the musculoskeletal systems. Muskuloskeletal decline is characterized by decreased functional ability occurs due to knee osteoarthritis. To improve functional abilities with exercise therapy using elastic band. Research Objective: Identify the effect of exercise therapy with elastic band on functional abilities of elderly with knee osteoarthritis. Research methods: research design in pre-experimental. Exercise therapy using elastic band were given to 20 respondents. Selected purposive sampling of the age range of >60 years with positive measurement of knee osteoarthritis. Data collection by interview using KOOS to measure respondents ability of independence. Results: Average KOOS score before intervention 41,87 and after intervention 51,29. Paired Sample T Test retruns p value = 0,0001<ɑ(0,05). Conclusion: There is effect of exercise therapy intervention using elastic band on functional abilities of elderly with knee osteoarthritis.